On the Question of the Ideology of the Eurasian Economic Union - S. Yu. Glazyev; I. F. Kefeli (Евразийская интеграция: экономика, право, политика)
Aim. To update attention on the need to form the ideology of Eurasian integration, expressing not only economic, but also common socio-political and spiritual interests and a vision of the common future of the EAEU.Tasks. To reveal the essence of the ideology of Eurasian nationalism, the value content of the concept of the Community of the Common Destiny of Humanity and the possibility of their complementary integrity in the ethno-political continuum of Greater Eurasia.Methods. Civilizational and concrete-historical approaches, as well as axiological discourse regarding the ideological choice in a multi-ethnic community.Results. The enduring value of the concepts of Eurasian nationalism, inverted in relation to modernity, and the Community of the Common Destiny of Mankind is substantiated. The main directions of the search for theoretical and axiological foundations are determined.Conclusion. On the agenda of Eurasian integration is the search for conditions for the rejection of libertarian ideology, serving the interests of international capital, and not peoples with a common historical destiny. It is necessary to search for its own kind of social-conservative synthesis, which combines the restoration of socialist ideology with the spiritual traditions of the Eurasian peoples.